9 From the Nine Worlds : Magnus Chase and the Gods of Asgard - Riordan, Rick (London Puffın Books, 2018)
Travel the Nine Worlds with your favourite characters from the world of Magnus Chase in a brand-new series of adventures. Find out why Amir Fadlan hates clothes shopping in Midgard, see how Mallory Keen learns in icy Niflheim that insulting a dragon can be a good idea, and join Alex Fierro as they play with fire (and a disco sword) in the home of the fire giants, Muspellheim. But watch out for Thor, who is jogging through all Nine Worlds so he can log his million steps - and is raising quite a stink . . .